Cytokines' Impact on Postpartum Hair Loss After First C-Section in Women 28-38: Dampak Sitokin terhadap Kerontokan Rambut Pasca Persalinan Setelah Operasi Caesar Pertama pada Wanita 28-38 - Almohaisen, Farooq L.J.; Hadi, Abdulrhman M. Hassan; Kadhim, Shaymaa Jawad; Mohsein, Osama A. (Universitas Muhammadiyah Sidoarjo, 2025)
Background; Postpartum hair loss is a common condition affecting women after childbirth, particularly in those who have undergone cesarean delivery. Cytokines, which are key regulators of immune responses, are believed to play a significant role in the pathogenesis of this condition by influencing the hair growth cycle and immune function during the postpartum period. Aims of the study; Investigate the role of cytokines, including IL-6, TNF-α, IL-10, and CRP, in postpartum hair loss in women aged 28-38 after their first cesarean delivery, and to explore their potential correlation with changes in thyroid function and lipid profiles during the postpartum period. Methodology; This cross-sectional study aimed to determine biomarker levels in women aged 28-38 after their first cesarean section. It included 150 participants: 100 women post-first cesarean and 50 healthy controls. Ethical approval was obtained, and informed consent was given by all participants. Exclusion criteria included multiple cesarean sections, chronic diseases, or medication affecting biomarkers. Blood samples were collected after an overnight fast, and biomarkers like IL-6, TNF-α, IL-10, CRP, adiponectin, FBS, lipid profile, TSH, and Free T3 were measured using appropriate assays. Statistical analysis was performed, with p < 0.05 considered significant. Result; The comparative results between patients (n=100) and healthy controls (n=50) showed no significant difference in age (33.5 ± 3.4 vs. 30.2 ± 3.1 years, p=0.12). However, patients had a significantly higher BMI (29.5 ± 3.2 kg/m²) compared to controls (26.1 ± 3.0 kg/m², p<0.001). Levels of inflammatory markers (IL-6, TNF-α, IL-10, CRP) were significantly higher in patients (p<0.001), while adiponectin levels were lower (14.2 ± 7.5 ng/mL vs. 20.8 ± 9.1 ng/mL, p=0.02). Metabolic markers such as fasting blood sugar, cholesterol, triglycerides, and LDL-C were significantly elevated in patients (p<0.001). The severity of hair loss was also greater in patients (p<0.001). Additionally, TSH levels were significantly higher in patients (p=0.02), while Free T3 showed no significant difference (p=0.12). Conclusions; In conclusion, elevated inflammatory markers (IL-6, TNF-α, IL-10) and metabolic disturbances (higher BMI, fasting blood sugar, cholesterol) in postpartum women after cesarean delivery may contribute to hair loss. These alterations reflect the body's response to stress and hormonal changes following delivery. Highlights: Inflammatory Response & Hair Loss – Elevated levels of IL-6, TNF-α, IL-10, and CRP in postpartum women after cesarean delivery suggest a strong link between inflammation and hair loss. Metabolic & Hormonal Changes – Higher BMI, increased fasting blood sugar, cholesterol, and TSH levels indicate metabolic disturbances that may contribute to postpartum hair loss. Clinical Implications – Understanding these biomarker changes could help in developing targeted interventions to manage postpartum hair loss and associated metabolic risks. Keyword: Postpartum, Cesarean Delivery, Inflammatory Markers, Hair Loss, Metabolic Disturbances, Hormonal Changes